Calidad del servicio y la satisfacción del cliente en el restaurante Huasai 2022 - Rios Rojas, Fiorella Geraldine (2023)
The purpose of the research is to determine the relationship between service quality and customer satisfaction in the Huasai restaurant in 2022 in order to improve customer satisfaction in the city of Iquitos in 2021. The methods used are quantitative, descriptive in nature and correlational. According to the research variables applied to customer service, most food service companies are based on the dimensions of satisfaction, effectiveness and trust, and to achieve satisfaction a series of infrastructure, texture and price of food are required. sale. be associated with a requirement. Maintain customer requirements and quality standards of the service with which they carry out transactions. We also ensure that our employees have the skills and ability to confront problems and resolve them in the most beneficial way, are experienced in providing services in a pleasant manner, are determined, friendly and provide good treatment. An individual's ability to convey warmth.